Development and delivery of bean varieties in Africa: the Pan-Africa Bean Research Alliance (PABRA) model - Buruchara, Robin Arani; Chirwa, Rowland; Sperling, L.; Mukankusi, Clare Mugisha; Rubyogo, Jean-Claude; Muthoni Andriatsitohaina, Rachel; Abang, Mathew M. (2011)
Common bean (Phaseolus vulgaris L.) has evolved rapidly in Africa and is steadily transforming from a traditional subsistence to a market-oriented crop, with major impacts on household incomes, food and nutritional security, and national economies. However, these benefits are yet to be felt in many parts of the continent because of multiple constraints that limit bean productivity. The Pan-Africa Bean Research Alliance (PABRA) has been at the forefront of efforts to accelerate the transition of beans from a subsistence crop to a modern commodity in Sub-Saharan Africa. This paper presents a unique partnership model and the breeding and seed delivery strategies used by PABRA to reach millions of beneficiaries with improved bean varieties. The breeding strategy involved the paradigm shift from a monolithic approach where varieties were bred for yield or resistance to single environmental stresses, to a grain type-led and market-driven approach. The PABRA model comprises partnerships between and among Centro Internacional de Agricultura Tropical (CIAT), National Agricultural Research Systems (NARS), public and private sector actors along the varied bean product value chains, and technology end-users. This model led to the release of over 200 varieties during 2003-2011, including beans with resistance to multiple constraints (biotic and abiotic), high iron and zinc content, and those for specific niche markets. PABRA reached 7.5 million households with seed of improved bean varieties during 2003– 2008 and is expected to reach an additional 14 million by 2013. From this undertaking, aspects that lend to policy recommendations to key stakeholders in the common beans value chain include: facilitation of access to credit; promotion of breeder and foundation seed production; easing of restrictions on the release of varieties; facilitation of collective marketing schemes; and deliberate policy frameworks to encourage the use of complementary integrated crop management practices.